Structure Optimization of Rib Drill Pipe Based on Gas-Solid Coupling and Orthogonal Experiment. (12th December 2020) - Li, Jia; Li, Dongmin; Zhong, Peisi; Ma, Guofang; Luan, Hengxuan; Xia, Shangfei
Abstract : At present, drilling rig is a common equipment for controlling gas outburst generated in underground coal mine, and rib drill pipe is an important component of drilling rig. Due to the insufficiency of slag discharge capacity, pipe-sticking accidents often occur during the drilling process, which greatly reduces the effect of gas control. In order to improve the capacity of slag discharge of rib drill pipe, the mechanism of slag removal was analyzed, and the process of slag discharge was simulated as a gas-solid two-phase flow coupling process. Utilizing the computational fluid dynamics method, the process of slag discharge was simulated on the Edem-Fluent cosimulation platform. The structural parameters of the drill pipe affecting the capacity of slag discharge were derived. Based on the analysis results, the structural parameters of rib drill pipe were optimized by orthogonal experiment method. The global optimal results were obtained as follows: its pitch, blade height, and blade width are 120 mm, 3 mm, and 15 mm, respectively. Therefore, the results of slag discharge experiment on the optimum structure of rig drill pipe show that the slag discharge efficiency is increased by 11.38%, which effectively resolves the pipe-sticking problem.